Dibenzo‐α‐pyrones: a new class of larvicidal metabolites against Aedes aegypti from the endophytic fungus Hyalodendriella sp. Ponipodef12. Issue 7 (5th January 2017) - Mao, Ziling; Lai, Daowan; Liu, Xunda; Fu, Xiaoxiang; Meng, Jiajia; Wang, Ali; Wang, Xiaohan; Sun, Weibo; Liu, Zhi Long; Zhou, Ligang; Liu, Yang
Abstract: BACKGROUND: In our search for new agrochemicals from endophytic fungi, the crude extract of the endophytic Hyalodendriella sp. Ponipodef12 associated with the hybrid 'Neva' of Populus deltoides Marsh × P. nigra L. was found to possess larvicidal activity against Aedes aegypti . RESULTS: Fractionation of the extract has led to the isolation of 11 dibenzo‐α‐pyrones (1–11), including three new congeners: hyalodendriols A–C (1–3). The structures of the new compounds were elucidated by comprehensive spectroscopic analyses, including the modified Mosher's method for the assignment of the absolute configuration. Compounds2–7 showed potent larvicidal activities against the fourth‐instar larvae of A. aegypti with IC50 values ranging from 7.21 to 120.81 µg mL −1 . Among them, penicilliumolide D (6) displayed the strongest activity (IC50 = 7.21 µg mL −1 ). A structure–larvicidal activity relationship was discussed. The possible mode of action of these compounds was assessed for their acetylcholinesterase inhibitory activities. In addition, hyalodendriol C (3) displayed antibacterial activity against Bacillus subtilis and Xanthomonas vesicatoria, and exhibited strong inhibition against the spore germination of Magnaporthe oryzae . CONCLUSION: Our study revealed dibenzo‐α‐pyrones to be a new class of larvicidal metabolites against A. aegypti . © 2016 Society of Chemical Industry